Analisa Economizer Dalam Ruang Pembakaran Ketel Uap Pada Pabrik CPO - Lelawati Lelawati (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2021)
A steam boiler is a device that works by heating water to a boil to produce high pressure hot steam. The drum is made of forged steel DIN 17100, St 37-1 with a tensile strength of 240 N / mm² = 240 kg / cm². In the palm oil processing industry CPO (Crude Palm Oil) the hot steam produced by the steam boiler is used to drive steam turbines, as source of electrical energy, oil palm boiling, and other palm oil processing processes.The economizer is part of a steam boiler which serves to heat water for filling the kettle so that it reaches its boiling point.